2005
DOI: 10.1097/01.pec.0000181420.56729.4f
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Visits in a Pediatric Emergency Department and Their Relationship to the School Calendar

Abstract: The current study supports previous research findings of an association between the school year and child and adolescent mental health emergencies. In the current study, the school year appears to exacerbate childhood problems, as there is a greater frequency of psychiatric emergencies while children are in school. Implications for ED program development and school-based mental health service delivery are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 11 publications
2
19
1
Order By: Relevance
“…This period was chosen because it represented the most currently available data and because this length of time would account for any seasonal variation in ED psychiatric visits. 20 Claims data for children aged between 0 and 18 years with Medicaid in the following groups were included in the analysis: children who had an International Classification of Diseases, Ninth Revision (ICD-9) psychiatric diagnosis code (ie, having one of the ICD-9, Clinical Modification [ICD-9-CM] diagnoses 290.00-316.99), children who received a psychiatric procedure (ie, Current Procedural Terminology [CPT] codes 90801-90899), or children who were discharged to a psychiatric hospital after an ED visit.…”
Section: Methodsmentioning
confidence: 99%
“…This period was chosen because it represented the most currently available data and because this length of time would account for any seasonal variation in ED psychiatric visits. 20 Claims data for children aged between 0 and 18 years with Medicaid in the following groups were included in the analysis: children who had an International Classification of Diseases, Ninth Revision (ICD-9) psychiatric diagnosis code (ie, having one of the ICD-9, Clinical Modification [ICD-9-CM] diagnoses 290.00-316.99), children who received a psychiatric procedure (ie, Current Procedural Terminology [CPT] codes 90801-90899), or children who were discharged to a psychiatric hospital after an ED visit.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that youth who present with anxiety or somatic complaints are unlikely to have had an outpatient mental health provider. Because of the significant high rate of school attendance in these youths and an association between the school year and emergency mental health visits (27,28), the mental health units require improvement in schools as well as in hospitals. Routine screening for anxiety or somatic complaints in schools can facilitate earlier detection of atrisk individuals, thereby leading to a more appropriate use of the PES.…”
Section: Discussionmentioning
confidence: 99%
“…Despite literature that identifies the unique complexities of psychiatric and pediatric populations and recommends evaluation by specialty personnel, most general EDs do not have regular staff who are behavioral health specialists or pediatric specialists, much less pediatric behavioral health specialists. 11,13 Furthermore, studies have shown that dissimilarities between staff and patients' cultural backgrounds affect ED PES utilization. 2 Researchers suggest that less treatment seeking and lower satisfaction among minority patients occur in part because they are being treated by nonminority providers.…”
Section: Pediatric Mental Health Emergenciesmentioning
confidence: 99%
“…Investigators who have conducted reviews of the pediatric PES literature identify critical study limitations including sampling constraints and measurement issues. [16][17][18] Internationally, validated best practice standards for ED PES do not exist, 13 but a review of existing research reveals distinctive indications of such that guided the identification of relevant structure, process, and outcome variables. The literature offers several service recommendations such as utilizing specialty personnel, addressing cultural disparities, implementing standardized assessment instruments, improving communication between the mental health and medical staff, providing more information to families, improving the uniformity of data collection, and increasing the quantity of research efforts.…”
Section: Pediatric Mental Health Emergenciesmentioning
confidence: 99%